Empowering Farmers Through Innovation in Plant Clinic Development - Rachmawatie, Dessy (Indonesian Journal Publisher, 2024)
This service aims to increase farmers' knowledge of how to control pests and diseases of rice plants by developing a plant clinic in Sumber Village, Trucuk District, and Klaten Regency. So that farmers have increased knowledge and capacity in dealing with the problems of controlling pests and diseases of the rice plants they manage. The community service method is counseling and direct interviews with the Association of Farmers Groups (GAPOKTAN)